Determinants of heterosexual men's demand for long-acting injectable pre-exposure prophylaxis (PrEP) for HIV in urban South Africa - Cheng, Chih-Yuan; Quaife, Matthew; Eakle, Robyn; Cabrera Escobar, Maria A.; Vickerman, Peter; Terris-Prestholt, Fern (BMC public health, 2019)
Heterosexual men in South Africa are a large key population to exposure to HIV, yet preferences for HIV pre-exposure prophylaxis (PrEP) among this population have not, to date, been investigated in the literature. This paper aims to explore HIV prevention preferences among heterosexual men in urban South Africa, as well as to examine the demand and characteristics of men who favour long-acting injectable (LAI) PrEP over condoms and oral PrEP.